Epidemiologic Assessment of Pediatric Inflammatory Bowel Disease Presentation in NYC During COVID-19. Issue 5 (19th February 2023) - Rosenbaum, Janet E.; Ochoa, Kenny Castro; Hasan, Faria; Goldfarb, Alexa; Tang, Vivian; Tomer, Gitit; Wallach, Thomas
Abstract : Inflammatory bowel disease (IBD) pathogenesis is thought to be induced by a mix of genetic susceptibility, microbial populations, and immune triggers such as infections. Severe acute respiratory syndrome coronavirus 2 (SARS-nCoV2) may have increased capacity to generate autoimmune disease as evidenced by known spikes in diseases such as type 1 diabetes mellitus. Public health interventions like masking and closures additionally created remarkable drops in typical viral infections, with remarkable shifts in influenza-like illness reporting in 2020. This study aims to evaluate the impact of SARS-nCoV2 and associated interventions on pediatric IBD presentation in New York City using records of new diagnoses at a consortium of 4 institutions between 2016 and June 2022. We fit time series model (autoregressive integrated moving average model) to monthly and quarterly number of cases of each disease for January 2016–March 2020 and forecast the period between April 2020 and June 2022. We note no decrease in ulcerative colitis (UC) or Crohn disease (CD) in the aftermath of historic low levels of overall viral illness, and statistically significant increases in CD diagnoses and elevation in UC diagnoses creating a trend suggesting overall increase in IBD diagnoses exceeding the baseline rate of increase. These data suggest a possible linkage between SARS-nCoV2 infection rates and subsequent pediatric IBD presentation.